Adaptation and intertextuality - Cadavid, Alvaro (Íkala, Revista de Lenguaje y Cultura, 2000)
The debate surrounding the place of literature in cinema is directly related to the problem raised by intertextuality, inasmuch as the text or discourse of the film version of a literary work begins by either basing itself or differentiating itself from another text(s). In the following article, the author seeks to distance himself from two polarised positions. One such position is to be found in those studies that aim to prove the superiority of symbolic representation present in literature over that present in other artistic mediums. Such a stance is opposed by countless cinema critics and theorists who argue instead that storytelling and artistic representation are best conveyed through the cinema. In the author's view both positions are based on subjective preferences and as such can only lead to petty, sterile debates of little academic interest.